Estudo sobre a atividade antifúngica e antioxidante de extratos de própolis obtidos com CO2 supercrítico - Fianco, Ana Luisa Butelli (2014)
Propolis is a resinous substance produced by bees through the collection of plant secondary metabolites and its chemical composition is complex and varied, giving this product several biological activities such as antibacterial, antifungal and antioxidant. The propolis extract can be obtained by supercritical fluid extraction using CO2 as solvent, which is a clean and non-toxic technology, leaving no residue. This work aims to extract chemically and biologically extracts of green and red propolis produced by bees of the species Apis mellifera. Supercritical CO2 extraction from the raw propolis and its ethanolic extracts, which were impregnated in filter papers, were performed. The pressures used for fractionation of raw propolis were 90, 120, 150, 200, 250 and 300 bar and, for the propolis impregnated in filter papers, 90, 150 and 300 bar. For comparison of the chromatographic profiles at different pressures, chemical analysis using Thin Layer Chromatography (TLC) and High Performance Liquid Chromatography (HPLC) were done. The chemical composition of the extracts from impregnated propolis ethanolic extracts (PEE) and raw propolis remained similar, but the yield of supercritical extracts from impregnated PEE in filter papers showed much higher values. Supercritical extracts showed antifungal activity and excellent antioxidant activity.